Türk medeni hukukunda üst hakkı - Işıkal, Alper (My University, 2023)
Ülkemizde genellikle hukuki ve ekonomik riskleri daha az olduğu için, arsa malikleri ile yatırımcılar üst hakkı sözleşmesi yerine arazi alım satım sözleşmesi yapmayı veya aynı gerekçelerle kat karşılığı inşaat sözleşmesi veya hasılat paylaşımı sözleşmesi yapmayı tercih etmektedirler. Bundan dolayı da özel hukuk kişileri arasında uygulamada üst hakkına nadiren rastlanmaktadır. Genellikle taşınmaz maliki olarak bir tarafın kamu idaresi, diğer tarafın da özel hukuk kişisi yatırımcı hallerde taraflar arasında üst hakkı sözleşmeleri yapıldığına tanık olunmaktadır. Biz bu çalışmamızda temelde üst hakkını ele alacağız. Ancak özellikle üst hakkı sözleşmelerinin bir tarafının kamu idaresi olması halinde taraflar arasındaki ilişkinin hususiyet arz eden yönlerini de inceleyeceğiz. Kamu Hukuku mevzuatında düzenlenen üst hakkı hükümleri ile Türk Medeni Kanunu’nda düzenlenen üst hakkı hükümleri arasında çelişen durumlar mevcuttur. Kamu hukuku mevzuatında, üst hakkı ile ilgili olarak, Türk Medeni Kanunu’na uygun şekilde bir genel hukuki düzenleneme yapılması uygun olur. Bu hususta bizim tavsiyemiz; üst hakkına ilişkin düzenlemeleri içeren tüm kamu mevzuatına, yüklü taşınmaz malikinin ve üst hakkı sahibinin Türk Medeni Kanunu’nda belirtilen haklara sahip olduğu şeklinde açıklayıcı ek bir madde eklenmesidir.

Because of the legal and economic risks are generally less in our country, land owners and investors prefer to make a land purchase and sale contract or for the same reasons a construction contract in return for flat or revenue sharing contract instead of a right of construction contract. For this reason, the right of construction is rarely encountered in practice among private law persons. Generally, it is witnessed that the right of construction agreements is made between the parties, in cases where one party as the real estate owner is the public administration and the other party is the private legal person investor. In this study, we will basically cover the right of construction. However, we will also examine the special aspects of the relationship between the parties, especially if one party of the right of construction agreements is the public administration. There are conflicting situations between the provisions of the right of construction regulated in the Public Law legislation and the provisions of the right of construction regulated in the Turkish Civil Code. In the public law legislation, it would be appropriate to make a general legal arrangement in accordance with the Turkish Civil Code regarding the right of construction. Our recommendation in this regard; to add an additional explanatory article to all public legislation containing the regulations regarding the right of construction, stating that the owner of the loaded immovable and the owner of the right of construction have the rights specified in the Turkish Civil Code.
Keywords: Building; Civil law; End of Right of Construction; Immovable Property; İnşaat; Loaded Immovable; Medeni hukuk; Owner of the Loaded Immovable; Owner of the Right of Construction; Real Estate; Right of Construction Agreement; Superficies; Taşınmaz Mal; Üst hakkı; Üst Hakkı Sahibi; Üst Hakkı Sözleşmesi; Üst Hakkının Sona Ermesi; Yapı Right of Construction; Yüklü Taşınmaz; Yüklü Taşınmaz Maliki